Single‐Dose Pharmacokinetics and Safety of Solriamfetol in Participants With Normal or Impaired Renal Function and With End‐Stage Renal Disease Requiring Hemodialysis. (13th March 2019) - Zomorodi, Katie; Chen, Dan; Lee, Lawrence; Lasseter, Kenneth; Marbury, Thomas
Abstract: Solriamfetol (JZP‐110), a selective dopamine and norepinephrine reuptake inhibitor with wake‐promoting effects, is renally excreted ∼90% unchanged within 48 hours. Effects of renal impairment and hemodialysis on the pharmacokinetics and safety of 75‐mg single‐dose solriamfetol were evaluated in adults with normal renal function (n = 6); mild (n = 6), moderate (n = 6), or severe (n = 6) renal impairment; and end‐stage renal disease (ESRD) with and without hemodialysis (n = 7). Relative to normal renal function, geometric mean area under the plasma concentration–time curve from time zero to infinity increased 53%, 129%, and 339%, and mean half‐life was 1.2‐, 1.9‐, and 3.9‐fold higher with mild, moderate, and severe renal impairment, respectively. Renal excretion of unchanged solriamfetol over 48 hours was 85.8%, 80.0%, 66.4%, and 57.1% in normal, mild, moderate, and severe renal impairment groups, respectively; mean maximum concentration and time to maximum concentration did not vary substantially. Decreases in solriamfetol clearance were proportional to decreases in estimated glomerular filtration rate. Geometric mean area under the plasma concentration–time curve from time zero to time of last quantifiable concentration increased 357% and 518% vs normal in ESRD with and without hemodialysis, respectively, with half‐life >100 hours in both groups. Over the 4‐hour hemodialysis period, ∼21% of solriamfetol dose was removed. Adverse events included headache (n = 1) and nausea (n = 1). Six days after dosing, 1 participant had increased alanine and aspartate aminotransferase, leading to study discontinuation. While these adverse events were deemed study‐drug related, they were mild and resolved. Results from this study combined with population pharmacokinetic modeling/simulation suggest that solriamfetol dosage adjustments are necessary in patients with moderate or severe but not with mild renal impairment. Due to significant exposure increase/prolonged half‐life, dosing is not recommended in patients with ESRD.